Maqaṣid Al-Syari‘ah Sebagai Fondasi Etika Ekonomi Digital (Kritik Filosofis terhadap Kapitalisme Berbasis Teknologi) - Putri Aulia; Nabila Islami Putri Irawan; Hevi Hentika Sari; Havis Aravik (TOMAN: Jurnal Topik Manajemen, 2026)
The rapid development of the digital economy has significantly transformed the global economic system through the extensive use of digital technologies, data, and algorithm-based platforms. However, the dominance of technology-based capitalism within the digital economy has also generated various ethical challenges, including data exploitation, unequal distribution of economic value, and the erosion of human dignity. This article aims to analyze Maqāṣid al-Sharī‘ah as an ethical foundation for the digital economy and to explore an Islamic philosophical critique of technology-driven capitalism. This study employs a qualitative approach using library research and normative-philosophical analysis of relevant academic literature published between 2015 and 2025. The findings indicate that digital capitalism primarily prioritizes efficiency and profit accumulation, often at the expense of justice and social welfare. Maqāṣid al-Sharī‘ah, which emphasizes the protection of religion, life, intellect, lineage, and property, offers a comprehensive ethical framework to evaluate and guide digital economic practices toward greater justice and human-centered development. This article argues that the integration of Maqāṣid al-Sharī‘ah into the digital economy must be systemic and substantive rather than merely formal, ensuring that digital technology serves as a means to achieve collective well-being (falah) and sustainable social development.